Pengaruh Model Pembelajaran Inkuiri terhadap Motivasi Belajar Siswa pada Mata Pelajaran Biologi - Diana, Rachel; Febriyanti, Arita (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This research is motivated by the implementation of learning conditions that still use lecture-based or conventional learning models. The learning process carried out is more centered on educators, while students only receive the learning materials provided. This causes a lack of student motivation in learning. Therefore, educators are required to use a variety of learning models in order to optimize the learning process. The purpose of this study was to determine the effect of the inquiry learning model on student learning motivation at SMAS Global Madani. This research is a quantitative study with a quasi-experimental method. The number of samples in this study was 50 respondents consisting of 25 respondents for class X1 and 25 respondents from class X2. The sampling technique in this study used purposive sampling technique. This study uses primary data, which is collected by distributing questionnaires. The results showed that the average value for the control group was 77% in the good category, and for the experimental group 74%, also in the good category. This shows that there is an effect of the inquiry learning model on student learning motivation at SMAS Global Madani.